The Mediating Role of Loyalty Between Gaming Addiction and the Intention to Purchase Online Mobile Apps - Wassil Elanguoud; Ilham El haraoui; Youssef Khatori; Mohammed Aqqaoui (Ianna Journal of Interdisciplinary Studies)
Background: Game developers' revenue greatly relies on in-game purchases, which are influenced by consumer experience, lifestyle, and perceived risk. Nevertheless, the increasing prevalence of addiction to online mobile gaming has raised concerns about how it could affect player behaviour and the market as a whole.